Integrasi Teknologi Desain Grafis dalam Pelestarian Budaya: Peningkatan Kreativitas Mahasiswa Melalui Motif Batik Kalimantan Timur - Muhlis, Muhlis; A, Sainal; Sultan, Muhammad; Ridwan; Irwanto; Galluci, Angga; Alif Tunru, Andi; Rachmadani, Andry; Aulia Rahman, Muhammad (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service program focuses on providing graphic design training to enhance the creativity of students in Biduk-Biduk Village, Berau Regency, East Kalimantan. The training utilizes CorelDraw and Photoshop as primary tools for developing decorative batik motifs that reflect local cultural heritage. In addition to improving technical skills, this activity aims to foster students’ awareness and active participation in preserving regional cultural identity. The program was implemented using an educational approach that combines lectures, interactive discussions, and hands-on practice to ensure comprehensive understanding. The implementation was structured into several stages, including preparation, execution, evaluation, and follow-up to ensure program sustainability. The training materials covered the introduction of design software features, understanding of East Kalimantan batik motifs, application techniques, and evaluation of participants’ design outputs. Through this activity, participants not only gained conceptual knowledge but also developed the ability to independently create graphic design products. Therefore, this program serves as a strategic effort to integrate digital technology with the preservation and development of local culture.